AN ERROR ANALYSIS ON ENGLISH DIPHTHONGS PRONUNCIATION BY BANYUMASAN JAVANESE SPEAKERS IN INDONESIA - Anindita, Maharani Laksmi; Munandar, Aris (Premise: Journal of English Education and Applied Linguistics, 2025)
First language interference is when a speaker transfers their L1 systems into L2. In Indonesia, vernacular could also cause interference. However, no research has been conducted to analyze the interference of L1 Banyumasan Javanese. This research analyzes English diphthong pronunciation errors due to interference in the Banyumasan Javanese language. This research is descriptive qualitative research, and the participants are ten L1 Banyumasan Javanese junior high school students. The data is participants' pronunciation of English diphthong sounds, and the data collection method is recording. Error analysis (EA) is used to analyze the data. The result showed that the diphthong [aʊ] has the least number of participants that pronounced incorrectly, and diphthong [ɪә], [eә], and [ʊə] are the most difficult for the Banyumasan Javanese speaker participants. The phonological error types are sound omission and substitution. The linguistic factor that caused the error is the difference in the phonological system between the Banyumasan Javanese and English languages. The difference in diphthong inventory caused the participants to substitute the diphthong with a monophthong sound similar to L1 Banyumasan Javanese. In contrast, the difference in the frequency of use of the diphthongs, where Banyumasan Javanese is more dominated by monophthongs, caused the participants to have difficulty in pronouncing complex diphthong sounds and eventually simplified the diphthong by omitting the last vowel of the diphthong. The result of this study could be used to consider phonology as one of the main focuses in English language teaching.